Factors Affecting Detection of Hepatitis E Virus on Canadian Retail Pork Chops and Pork Livers Assayed Using Real‐Time RT‐PCR. (20th July 2015) - Wilhelm, B. J.; Leblanc, D.; Avery, B.; Pearl, D. L.; Houde, A.; Rajić, A.; McEwen, S. A.
Summary: We collected 599 Canadian retail pork chops and 283 pork livers routinely (usually weekly) from April 2011 to March 2012 using the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) retail sampling platform. Samples were assayed using validated real‐time (q) reverse transcriptase polymerase chain reaction (RT‐PCR) and nested classical RT‐PCR for the detection of hepatitis E virus (HEV), porcine enteric calicivirus (PEC) and rotavirus (RV). The presence of Escherichia coli, Salmonell a spp. and Campylobacter spp. was measured on a subset of our samples. Exact logistic regression models were fitted for predictors for HEV detection, for each assay. For both assays, sample type (pork chop versus liver) was a significant predictor for HEV RNA detection. For nested classical RT‐PCR but not qRT‐PCR, region of sample collection was a significant predictor ( P = 0.008) of HEV detection. Odds of HEV detection were greatest in spring relative to other seasons. E. coli was a significant predictor for HEV RNA detection using the qRT‐PCR ( P = 0.03). Overall, the prevalence of E. coli, Salmonella spp. and Campylobacter spp. was significantly greater than HEV, PEC or RV on our retail pork samples. Our sparse data set for the detection of PEC and RV precluded modelling of risk factors for the detection of these viruses.